2013
DOI: 10.1609/aimag.v34i4.2512
|View full text |Cite
|
Sign up to set email alerts
|

Any‐Angle Path Planning

Abstract: In robotics and video games, one often discretizes continuous terrain into a grid with blocked and unblocked grid cells and then uses path-planning algorithms to find a shortest path on the resulting grid graph. This path, however, is typically not a shortest path in the continuous terrain. In this overview article, we discuss a path-planning methodology for quickly finding paths in continuous terrain that are typically shorter than shortest grid paths. Any-angle path-planning algorithms are variants of the he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 32 publications
3
60
0
1
Order By: Relevance
“…This article generalizes the approach taken by Nash (2012), to handle line segments at a finite number of gradients (Nash, 2012, assumed two gradients only).…”
Section: An Upper Bound On Inefficiency From Differences In Gradientmentioning
confidence: 99%
See 1 more Smart Citation
“…This article generalizes the approach taken by Nash (2012), to handle line segments at a finite number of gradients (Nash, 2012, assumed two gradients only).…”
Section: An Upper Bound On Inefficiency From Differences In Gradientmentioning
confidence: 99%
“…Nash's comprehensive study (2012, also see the overview in Nash & Koenig, 2013) considered grid paths on regular grids in two and three dimensions. His work was subsequently expanded by Bailey et al (2015) in the two-dimensional case to cover both 4-and 8-connected paths, with feasible locations at both cell corners and cell centers (they also studied the lengths of shortest vertex paths versus true shortest paths).…”
Section: Definitionmentioning
confidence: 99%
“…Pal et al [12] used the A* algorithm to generate efficient paths by adding a function of the energy consumption to an Euclidean metric, which is the cost function commonly used for motion planning. Nash et al [7], [8] stated that the A* algorithm generates the shortest path in the discrete environment (grids) but it is not always true in the continuous environment. Brandt [13] investigated the selfreconfiguration properties of the ATRON modular robot by applying A*.…”
Section: Other Related Workmentioning
confidence: 99%
“…On random 500 × 500 2D grids with 20% blocked cells, Basic Theta* finds paths shorter than A* with post smoothing techniques 70% of the time [7]. Nash et al [8] state that the paths found by A* on 26-neighbor cubic grids can be ≈ 13% longer than truly shortest paths. Basic Theta* can be easily extended to 3D grids because it is based on the triangle inequality.…”
Section: A Basic Theta*mentioning
confidence: 99%
See 1 more Smart Citation